Empowering melon fermers in Magelang through AI-Based smart greenhouse technology - Anton Yudhana; Novi Febrianti; Son Ali Akbar; Jihad Rahmawan; Julia Mega Reski (Universitas Ahmad Dahlan, 2025)
The application of technology in the agricultural sector is a strategic step in addressing the challenges of production efficiency and adaptation to climate change. This study presents a community empowerment initiative through the implementation of an AI-based control system in a smart greenhouse to improve melon productivity in Magelang. The community service program was conducted by Ahmad Dahlan University (UAD) in collaboration with the Rukuntani Farmers Group in Salam Village, Magelang, through the introduction and implementation of the Artificial Intelligence Farming Control System (AFAS) in a smart greenhouse. The system integrates environmental sensors and leaf image cameras with Artificial Intelligence (AI) algorithms and the Internet of Things (IoT) to monitor plant conditions and automatically detect diseases. The activities were carried out in stages, including needs assessment, training, system installation, and weekly mentoring. The results showed a 25% increase in melon productivity and more consistent fruit quality. In addition, farmers’ independence in operating the technology improved, and their work patterns shifted toward data-driven precision agriculture. This program demonstrates that a participatory approach supported by appropriate technology can have a significant impact on empowering farming communities and transforming local agriculture, as well as showing the potential of participatory smart farming programs in supporting sustainable agriculture in developing regions